Genomic Insights and Plant Growth-Promoting Potential of Rhizobial Strains from Agave americana - Luis Galdino García-Pérez; Clara Ivette Rincón-Molina; Esperanza Martínez-Romero; Marco Antonio Rogel; Yunuen Tapia-Torres; Luis Alberto Manzano-Gómez; Julio César Maldonado-Gómez; Francisco Alexander Rincón-Molina; Reiner Rincón-Rosales (Horticulturae)
Symbiotic relationships between plants and bacteria play a pivotal role in both natural and agricultural ecosystems, particularly through endophytic colonization or rhizospheric interactions. This study evaluated the plant growth-promoting potential (PGP) of native rhizobial strains Rhizobium sp. ACO-34A and Mesorhizobium sp. 28A (now reclassified within the genus Kumtagia), isolated from Agave americana. Through phenotypic characterization, PGP evaluation, and comparative genomic analysis, both strains demonstrated the ability to thrive under diverse salinity levels and pH conditions, reflecting their adaptability to challenging environments. Rhizobium sp. ACO-34A exhibited superior resistance to antibiotics and heavy metals, coupled with robust PGP traits, such as phosphate solubilization and indole-3-acetic acid (IAA) production, which are crucial for enhancing nutrient availability and root development. Similarly, Mesorhizobium sp. 28A showed exceptional phosphate solubilization efficiency and contributed to improved seedling performance. These findings highlight the capacity of rhizobia associated with agave species to improve plant growth, reduce dependence on chemical fertilizers, and support sustainable agriculture, particularly in nutrient-depleted or semi-arid soils. Genomic analyses revealed the presence of genes linked to stress resilience and nutrient acquisition, underlining the functional versatility of these strains. By leveraging these native rhizobial strains, agricultural practices can achieve higher productivity and sustainability, making them valuable tools for enhancing the agronomic yield and ecological resilience of agave crops for agro-industries.